0774 Night-sleep Duration Trajectories And Behavior In Preschool-aged Children From The EDEN Cohort. (12th April 2019) - Reynaud, Eve; Forhan, Anne; Heude, Barbara; Charles, Marie-Aline A; Plancoulaine, Sabine
Abstract: Introduction: The association between sleep and behavior has been extensively studied in adolescents and school-aged children, but very little attention has been given to preschoolers. A systematic review of the literature allowed us to identify 10 articles describing the link between sleep duration and behavior in preschool aged children, with only 2 from the same team using a longitudinal design. Methods: Within the French birth-cohort study EDEN, repeated measures of children's night-sleep duration were collected at age 2, 3 and 5-6 through parental questionnaires, and were used to model night-sleep duration trajectories. Behavior was assessed with the "Strengths and Difficulties Questionnaire" which provides 5 subscales measuring a child's conduct problems, emotional symptoms, peer relation problems, antisocial behavior and hyperactivity/attention problems. The behavioral subscales were dichotomized at the higher 25th percentile. Multivariable logistic regressions, adjusted for parents' socio-economic factors, parental characteristics, children's characteristics and sleep habits, allowed us to study in 1021 children (53.9% boys) the association between night-sleep duration trajectories from 2 to 5-6 and behavior at age 5-6. Results: Five distinct night-sleep duration trajectory groups were identified: short- (SS, &lt10hrs, 5.0%), medium-low- (MLS, &lt11hrs, 48.4%), medium-high- (MHS, &eq11hrs30, 37.0%), long- (LS, &ge11hrs30, 4.3%) and modifier sleepers (MS, i.e. LS then MLS, 5.3%). After controlling for potential cofounders and baseline behavior at age 2, children belonging to the SS and MLS compared to MHS trajectories had, at age 5-6, increased risk of presenting hyperactivity/ inattention problems. This was observed only in boys (OR 2.8, 95%CI [1.2-6.8], and OR 2.2 [1.3-3.6], respectively; ptrajectories-gender interaction =0.02). Conclusion: Results suggest that the persistence of night-sleep duration &lt11hrs/night in preschool years is positively associated with more hyperactivity/inattention behavior, especially among boys. Support (If Any): N/A